Construction and application of standardized training effect evaluation system for new nurses in operating room - Xiaoli Liu; Yanshu Wei; Jin Pei; Xiaozhou Wu (Health Care Science, 2023)
Abstract Background This study aims to develop and validate a Structured Training Effectiveness Evaluation (STEE) tool based on the Kirkpatrick model for newly graduated registered nurses in the operating room in China. Methods The first phase will involve focus group and individual interviews with nursing educators and newly graduated registered nurses selected using purposive sampling. The data will be analyzed thematically to identify key components necessary to develop the STEE tool. The second phase will develop and validate the STEE tool through a panel of experts using the Delphi method. The item weights will be determined with the analytic hierarchy process technique. The third phase will involve implementation and evaluation of the STEE tool with an exploratory, nonexperimental, and comparative analysis. Descriptive and inferential statistical analyses will be performed with SPSS version 23. Results The STEE tool for newly graduated registered nurses in the operating room will be useful for evaluating training effectiveness during standardized training. The results obtained with this tool will clarify the effectiveness of training, thereby helping transform nursing students into competent nurses. Conclusion In this way, this study will provide practical guidance for improving standardized training programs and help newly graduated nurses manage their transition to the clinical work environment and remain in their posts.